(untitled) (Mugda Medical College Journal, 2025)
Recently, based on an international consensus, the term The term “non-alcoholic fatty liver disease” (NAFLD) was replaced by “metabolic dysfunction-associated steatotic liver disease” (MASLD). Metabolic dysfunction-associated steatotic liver disease (MASLD) is closely associated with obesity and type 2 diabetes mellitus. Lifestyle interventions aiming at substantial weight loss and pharmacological intervention to achieve desired histological outcomes are cornerstones of management of MASLD. Among pharmacological interventions, originally developed as antidiabetic drugs, incretin mimetics and SGLT2 inhibitors were found to reduce steatosis and fibrosis. Certain incretin agonists effectively improve histological features of MASLD. On the other hand, despite mild weight gain, one PPARã agonist (pioglitazone) was found to improve MASLD with certain benefit on fibrosis. Furthermore, benefits of other drug options, which directly target hepatic lipid metabolism (e.g., lipogenesis inhibitors, FGF21 analogs) have also been highlighted. Some combination therapies were also proved beneficial. Our discussion is based on weight loss, glycemic control, reductions of liver enzymes and histological improvement. We have compared results from clinical trials of different drugs as well as systematic review and meta analysis. Mugda Med Coll J. 2024; 7(2): 119-126